Contributions of Trade Unionism to Sustainable Development: The Case of the IPLIDO-UTHGRA - Césari, María Susana; Bonelli, Johanna Maldovan; Russak, Mariana; Eggers, Jörg (European Journal of Sustainable Development, 2019)
For several decades it has been internationally recognized the role of unions in promoting sustainable development goals, especially in its economic, social and cultural dimensions. While the commitment to free association, social dialogue and collective bargaining are some of the main aspects of their actions, trade union organizations also work in other key areas to achieve social justice, such as access to information, education, health and gender equity. The Institute for Equal Opportunities (IPLIDO) of the Union of Tourism, Hotel and Gastronomy Workers of the Argentine Republic (UTHGRA) is a paradigmatic case on this path. In order to ensure equal opportunities for all people (based on the equal participation of men and women in the labor, economic, political, cultural and family) the IPLIDO has carried out several actions aimed at: strengthen ties in the community; build networks among non-governmental organizations, trade unions and public institutions; promote gender equality; disseminate information and train in pressing issues such as addictions, grooming and gender violence; and participate in the design and implementation of laws and public policies, among others. This paper addresses the strategies and actions carried out by the IPLIDO since its creation -in 2006-, highlighting its interaction with the public sector, international and civil society organizations, in order to promote rights and values in the trade union sphere and the community in general.